Perception of affordability of PR1MA project among the department of academic affairs staff of Universiti Malaysia Sabah (UMS), Kota Kinabalu, Sabah / Gloria Danius and Nurizan Mujim - Danius, Gloria; Mujim, Nurizan (2016)
1 Malaysia Housing Project (PR1MA) is one of the government initiatives to solve the housing issue in Malaysia. It focuses on middle income household to provide an affordable housing scheme. This project has been introduced by the Prime Minister of Malaysia, Datuk Seri Najib Tun Razak on 4th July 2011. The category of middle income is between RM2,500 to RM10,000 of monthly income. This study examined the perception of affordability of PR1MA project among the staff at the Departments of Academic Affairs staff of Universiti Malaysia Sabah (UMS), Kota Kinabalu, Sabah. It uses a random sampling of 66 respondents of the department. The sample size has been generated using Umar Sakaran that refer Krejcie and Morgan table that provides generalized for sample size. Data for this research has been collected using self-construct questionnaire that designed as open-ended question. Then, uses primary and secondary data. It shows 59.2 % of the respondent said that their perception is moderate and 22.7 % respondent is somewhat low. Therefore, it argues that most of the respondent does not agree with 1 Malaysia Housing Project (PRIMA). This research found that price level has positive relationship with affordability of middle income to buy PRIMA house. By having this initiative, it can help to reduce the housing problem, especially for middle income group in Malaysia. It's become a necessary for the government to take action to ensure PRIMA meet its objectives. Hence, it can give more information regarding PRIM A housing for responsible party to take action.